Association between healthy lifestyle choices and mental health among students: a cross sectional study - Yan Wang; Jiayu Zhang; Lihua Huang; Xiaonan Li; Yanyan Zhong (BMC Public Health)
Abstract Background The prevalence of mental health problems among college students, both domestically and internationally, has emerged as a significant public health concern. College students are in a period of transition to independent living. Adopting a healthy lifestyle can have advantageous effects on their overall well-being. Thus, this study aimed to investigate the impact of healthy lifestyle choices on mental health problems among college students in China. Methods We conducted a cross-sectional online survey of college students from 2021 to 2023 at a university in Wuhan (N = 1826) using the cluster sampling method. We employed Chi-square tests and binary logistic regression to evaluate the association between healthy lifestyle choices and mental health and identify other influencing factors. Results A total of 969 (53.1%) students met standard criteria for poor mental health. Multiple analysis revealed that personal characteristics including female (1.280[1.035—1.582]), obesity (2.015[1.278—3.175]), general or poor health status (1.738[1.380—2.188]; 4.265[1.125—16.165]), occasionally attending health knowledge lectures or paying attention to health books and information (1.376[1.055—1.795]), healthy lifestyle choices including occasionally or seldom eating breakfast (1.393[1.105—1.757]; 1.825[1.287—2.587]), occasionally or seldom getting enough sleep (2.800[2.179—3.597]; 3.544[2.209—5.685]), a poor or very poor irregular schedule (1.792[1.222—2.628]; 3.619[1.380—9.486]), seldom or no physical exercise (1.395[1.053—1.847]; 1.377[1.066—1.779]), and often smoking (3.320[1.281—8.604]) were identified as significant predictors of poor mental health. Conclusion The prevalence of poor mental health among college students was high. A few types of healthy lifestyles, such as a lack of health knowledge and physical exercise, seldom eating breakfast, not getting enough sleep, an irregular schedule, and chronic smoking were closely related to abnormal psychological health symptoms. Interventions such as health education knowledge lectures and regular exercise programs should be given to college students to improve their mental health.